Procambarus (Girardiella) holifieldi, a new species of crayfish (Decapoda: Cambaridae) from Alabama with a revision of the Hagenianus Group in the subgenus Girardiella - Schuster, Guenter A.; Taylor, Christopher A.; Adams, Susan B. (Zootaxa, 2015)
Procambarus (Girardiella) holifieldi, new species, is a primary burrowing crayfish from a low-lying field in Perry County, Alabama. It belongs to the Hagenianus Group in the subgenus Girardiella. The new species is morphologically most similar to Procambarus (Girardiella) barbiger. They differ in the size and shape of the caudal processes. Procambarus barbiger has a beard along the mesial margin of the palm of the chela, while the new species lacks the beard. In addition to the description of the new species, the Hagenianus Group is reviewed and new synonymies are provided. We demonstrate that a cephalic process is indeed present in the Hagenianus Group.